Analysis of equivalent widths of alluvial channels and application for instream habitat in the Rio Grande - León, Claudia A., author; Julien, Pierre, advisor (Colorado State University. Libraries, 2003)
Rivers are natural systems that adjust to variable water and sediment discharges. Channels with spatial variability in width that are managed to maintain constant widths over a period of time are able to transport the same water and sediment discharges by adjusting the bed slope. Methods developed to define equilibrium hydraulic geometry characteristics of alluvial channels are limited to steady state input variables. This dissertation examines how the channel slopes adjust in sequential reaches with different widths to achieve continuity of steady and unsteady water and sediment discharges. The four objectives of this dissertation are: 1) to develop analytical relationships between equilibrium slope and width or width-depth ratio under steady water and sediment discharges; 2) to develop a transient numerical model for constant input variables to simulate the changes in channel slope with time; 3) to develop a transient numerical model for unsteady water and sediment discharges to simulate the transient solution of channel slope; and 4) to apply the model to the middle Rio Grande and integrate the results in the evaluation of potential fish habitat restoration activities. Results of the analytical solutions indicate that wide channels require steeper slopes than narrow channels to transport the same water and sediment discharges. In addition, channel slope is highly dependent on sediment concentration. The analytical solutions are in good agreement with laboratory flume data previously published and field measurements from the middle Rio Grande. Transient simulations under constant discharge show similar results. In addition, the model provides an estimate of the time to reach equilibrium under constant water discharge. Transient simulations with variable discharge indicate that bed slope changes rapidly during floods. Long-term simulations of slope changes under variable water and sediment discharges compare better with the simulation under a constant flow close to the mean annual discharge than under constant large floods (e.g. discharge equaled or exceeded 10 % of the time, or discharge equal or close to the dominant discharge). Field applications to the middle Rio Grande show that the wide channel reach of the Bosque del Apache has a steeper slope than the narrow reaches. Numerical simulations of the Bosque del Apache reach from 1992 to 1999 are in very good agreement with field measurements. Despite the increase in slope in wide reaches, the results of the numerical simulations of the Bosque del Apache reach indicate that shallow depths and low velocities occur more frequently in wide and steeper reaches than in narrow reaches. It is likely that low velocities and shallow depths are more favorable for the habitat of the Rio Grande silvery minnow.
Keywords: civil engineering; geology